The influence of a single oral dose of morphine on some cognitive functioning parameters in patients with chronic pain treated with non-opioid analgesics - Andryszak, Paulina; Stachowiak, Andrzej; Włodarczyk, Krzysztof; Walecki, Piotr; Ziółkowski, Marcin; Gorzelańczyk, Edward Jacek (Medycyna Paliatywna/Palliative Medicine, 2010)
The recent studies in patients with chronic pain indicate that opioids have an ambiguous influence on cognitive and psychomotor functions. The aim of the study was to evaluate cognitive functioning of the patients with chronic pain treated with nonsteroidal anti-inflammatory drugs, in whom a single short-acting morphine dose was administered. The patients (n = 8) were orally supplied with a single dose of 10 or 20 mg morphine. The control group included patients (n = 9) with chronic pain who were still being treated with NSAIDs. In the patients examined, the pain intensity was evaluated with the use of the numerical rate scale (NRS), symptoms of depression and anxiety were evaluated with the use of the Hospital Anxiety and Depression Scale – HADS, and general mental state with the use of the Mini-Mental State Examination (MMSE). The neuropsychological examination was carried out by means of the Trial-Making Test A and B, the Stroop Test and the examination of eye movements. In the patients treated with morphine, tests were conducted before and 45 minutes after the application of the drug. In the first group, after 1 hour since the morphine application pain intensity lowered significantly (p = 0.016), the duration of part A of the TMT-A Test (p = 0.079) was shortened and the duration of the second part of the Stroop Test increased. The average latention time increased and the maximal saccade speed was lowered. The remaining cognitive parameters did not change after the drug application. Morphine applied orally influences the reduction of pain intensity, not significantly deteriorating the cognitive parameters evaluated with the Stroop Tests and the Trial Making Test B (TMT-B). It was also shown that morphine influences the improvement of psycho-motor parameters evaluated with the TMT-A test. These research studies also proved the influence of morphine on some complex sensor-motor processes in the saccadometric examination.